Geotourism and Geoconservation on the Isle of Wight, UK: Balancing Science with Commerce - Martin Simpson (Geoconservation Research)
The Isle of Wight has a rich and varied geological heritage which attracts scientists, tourists and fossil collectors, both private and commercial. Each party has a role to play in geoconservation and geotourism, but a policy on the long term curation of scientifically important specimens is essential to prevent future conflicts. A new code of conduct is recommended, based on the one adopted on the Jurassic Coast of Dorset. I have spent over 40 years living on the Island and working in the tourist industry running geology field-trips for both academics and tourists, and managing one of the longest running geological gift shops. I see the geological heritage and fossil sites as valuable geotourism assets, and envisage no problems with respect to the scientifically important material provided that a clear collecting policy is adopted, and the local museum generates funding to ensure that significant finds remain on the Island. A positive attitude is recommended in view of past experiences.